Fizjologia i rozrodczość kobiety w pismach Metodego z Olimpu i Ambrożego z Mediolanu - Mejzner, Mirosław (Vox Patrum, 2016)
Topics concerning women’s physiology and reproduction appear relatively rarely in the reflections of the Fathers of the Church. Most often they perpetuated the beliefs of ancient medicine, benefitting from the appropriate terminology. The originality of their reflection lies in trying to use the “scientific” facts within theological considerations (eg the creation of mankind and the Incarnation of the Son of God) and moral ones (eg the value of sexuality, fertility and parenthood). The scope of this article includes analysis of selected texts of Methodius of Olympus and those of Ambrose of Milan. Both authors had a deep medical knowledge of the issues and their works contain interesting examples related to female reproductive physiology. They were protagonists of an ideal of virginity, but yet, they preserved a positive assessment of fertility and marriage. Worthy of particular emphasis, in the works of Methodius, is the defense of the dignity of every unborn child, whom God himself creates and animates in the womb. The basis of the considerations in Symposium was a passage from Genesis 2: 21-24, to which he gave allegorical meaning, defining human sexuality and procreation as the typology of the divine and ecclesiastical realities. In turn, Ambrose undertook issues such as conception, prenatal development and the birth of a child, in the context of the exceptional role of Mary in the history of salvation and in the Incarnation of the Son of God. Theological considerations were an excellent opportunity for him to express moral teaching and pastoral care, and to provide very practical and helpful, medical and educational tips for women.